Marks' standard handbook for mechanical engineers - Marks, Lionel S.; Avallone, Eugene A.; Baumeister, Theodore (McGraw-Hill, 1987)
Gathers reference information on heat, strength of materials, machine elements, power, materials handling, transportation, shop processes, electronics, and instruments